Effect of annealing temperature on some physical properties of MgB2 by using the Hall probe ac-susceptibility method - Varilci, A.; Yegen, D.; Tassi, M.; Stamopoulos, D.; Terzioglu, C. (PHYSICA B-CONDENSED MATTER, 2009)
A commercially available powder of MgB2 is used as starting material for the examination of the influence of the annealing temperature on the properties of this intermediate-T-c superconductor. We performed scanning electron microscopy (SEM) and Hall ac-susceptibility measurements as a function of temperature and ac-field amplitude on samples annealed at 650, 750, 850 and 950 degrees C. The imaginary part of ac-susceptibility measurements is used to calculate both the inter-granular critical current density, J(c)(T-p) and density of pinning force, alpha(j)(0). It was observed that all T-c, J(c)(T-p) and alpha(j)(0) exhibit a non-monotonic behavior on the annealing temperature range studied in this work. T-c is measured to be 39.85 +/- 0.02 K and J(c)(T-p) is estimated to be as high as 60 A/cm(2) at 39.2 K for the sample annealed at 850 degrees C. The peak temperature, T-p, in the imaginary part of the ac-susceptibility curves shifts to lower temperatures with both decreasing the annealing temperature and increasing the amplitude of the ac-magnetic fields. A comparison of the experimental ac-susceptibility data with theoretical critical-state models that are currently available is performed. SEM investigations showed that the grain size increases, and the grain connectivity improves when the annealing temperature increases up to 850 degrees C. The possible reasons for the observed changes in transport, microstructure and magnetic properties due to annealing temperature are discussed. (C) 2009 Elsevier B.V. All rights reserved.